Arduino-Assisted robotic and coding applications in science teaching: Pulsimeter activity in compliance with the 5E learning model. (3rd April 2019) - Cakir, Nevin Kozcu; Guven, Gokhan
Abstract: The purpose of the current study is to design and develop an Arduino-assisted robotic and coding activity in compliance with the 5E learning model for middle school students to construct knowledge and realize learning in science teaching. The study was conducted on 6 th grade students attending a private middle school in Turkey in the second term of the 2018 and 2019 school year. Application of the designed activity was carried out in the science laboratory with the participation of 10 students who were the members of the STEM club. The activity was designed to teach the concept of pulse addressed within the subject of circulatory system in the science curriculum in line with the 5E learning model. With this activity developed, systematic contraction and relaxation movements of the heart while working were modeled through robotics and coding. In addition, through this activity, it was intended to introduce the students to coding, to improve their attitudes towards technology, to develop their information processing skills and to help them to relate the concept of pulse to daily life. In this way, the students were provided with opportunities to experience Arduino-assisted robotic and coding applications and to integrate such applications into their daily life.